All hands on deck: levels of dependence between the EU and other international organizations in peacebuilding. Issue 8 (17th November 2019) - Petrov, Petar; Dijkstra, Hylke; Đokić, Katarina; Zartsdahl, Peter Horne; Mahr, Ewa
ABSTRACT: The EU seeks extensive partnership with other international organizations when it comes to security challenges. This is puzzling as the EU relies for its resources mostly on its member states. The relations between the EU and other international organizations have thoroughly been studied, yet scholars rarely question the actual rationale for partnership. We start from resource dependency theory which explains that almost all organizations are dependent on the resources of their partners. Yet we extend this theory by distinguishing between macro, meso and micro-level dependencies. To illustrate resource dependencies between the EU and other international organizations, we analyse EU's peacebuilding policies in Kosovo, Mali and Armenia. By accounting for macro- and micro-level dependencies we provide a more holistic perspective than conventional meso-level explanations. Our contribution is therefore to expand the scope of the resource dependency theory and provide a framework to analyse dependencies between the EU and other international organizations.